EFL Students’ Use of Transition Signals in Essay Writing - Ariyanti Ariyanti (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2021)
This study is aimed to explore the use transition signals used by EFL students in essay writing in higher education level. Particularly, this essay will be conducted to English Language Education Study Program students at University of Widya Gama Mahakam Samarinda. This research is a qualitative study with content analysis research design where twenty-six comparison and contrast essays of the third semester students were analyzed by using coding which indicates transition signals used by students. Additionally, in-depth interview also applied to the students who are considered as less active users of transition signals in their writing in order to figure out deeper on what difficulties they found during writing the essay. The findings of this research reveal three major result i.e. most of students are succeed to use compare and contrast type of transition signals to compose their comparison and contrast essay, the students mostly use time order transition signals to make their essay coherent, and two out of twenty-six students have no transition signals to be used on their essays. Result from interview shows that the students still lack of understanding toward when, where, and what type of transition signals can be used for certain context. Pedagogical implication is discussed further in this research.